PENGARUH DIAPHRAGMATIC BREATHING EXERCISE TERHADAP PERUBAHAN RESPIRATORY RATE PADA PASIEN ASMA DI RUANG INTERNA II RSUD DR. R SOEDARSONO KOTA PASURUAN - Yuvita Dwi Rahmasari; Ni Wayan Dwi Rosmalawati; Mustayah Mustayah (Jurnal Keperawatan Terapan, 2021)
Bronchial asthma is a reversible narrowing or inflammation of the bronchi characterized by wheezing, coughing and increased respiratory rate. Handling of asthma can be done with pharmacological and non-pharmacological therapy. One of the non pharmacological therapies that can be done is diaphragmatic breathing exercise. The purpose of this study was to determine the effect of administration of diaphragmatic breathing exercise on changes in the respiratory rate in asthma patients. The research design used is Quasy Experimental with the type of Non-Equivalent Control Group design. The large sample taken was 14 respondents with incidental sampling technique. This study uses an analysis of the difference in the Paired T Test which shows a decrease in the respiratory rate, as evidenced by the treatment group's p-value of 0.00. Furthermore, the results of the Independent T Test showed no difference between the treatment and control groups, but clinically there was an effect of diaphragmatic breathing exercise on the decrease in the respiratory rate in the treatment group of 3.571 times per minute greater than the control group of 2.714 timer per minute. Diaphragmatic Breathing Exercise therapy is expected to be an alternative therapy for reducing tightness in asthma patients Keywords: Diaphragmatic Breathing Exercise, Respiratory Rate, Asthma